Tipologi Ruang Rumah Usaha Pengrajin Kain Sasirangan - Pertiwi, Aula Sekar Arum; Damayanti Asikin; Lisa Dwi Wulandari (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Sasirangan fabric artisans carry out the production process in their respective houses. The house not only functions as a living space but also as a production space. Sasirangan fabric is a typical craft from Sasirangan Village, Banjarmasin, which is a source of livelihood for the community. The local government has designated Sasirangan Village as a riverfront area so that the existence and uniqueness of artisans's houses are in danger of being lost. The purpose of this case study research on the spatial typology of artists' business houses is to identify the different types of business houses based on the stage of production and space utilization patterns. The analysis was conducted by arranging categories based on function, spatial relationship patterns, and spatial organization. The research results show that six spatial typologies of business houses were found based on their space utilization patterns.